TO A QUESTION ON SYMPTOMATIC TREATMENT OF ACUTE RESPIRATORY INFECTIONS - V.К. Tatochenko (Union of pediatricians of Russia, 2008)
The authors consider the symptomatic therapy of acute respiratory diseases among children. They also discuss the application efficiency and safety of the local vasoconstrictors (decongestants).Key words: acute respiratory diseases, symptomatic therapy, decongestants, children.